4
$\begingroup$

A population has $G$ good and $B$ bad elements, $G+B=N$. Elements are drawn one by one at random without replacement. Suppose the first good element appears on draw number $X$. Find a simple formula, not involving any summation from $1$ to $N$, for $E(X)$. Hint: Write $X-1$ as sum of $B$ indicators.

Ok, so we know in the first $X-1$ draws we only get bad elements. Let $I_j$ be $1$ if $j$th draw gives bad ball and $0$ otherwise. $X-1=I_1+I_2+ \cdots +I_{x-1}$, all of which have value $1$. $E(I_1)= \cdots=E(I_n)=B/N=(N-G)/N$. Now we can write $E(X)=E((X-1)+1)$ $=E(X-1)+E(1)=E(X-1)+1.$ I'm not exactly sure on the formula for $E(X-1)$. Hopefully, I'm on the right track. Thanks!

$\endgroup$
  • $\begingroup$ @MikeSpivey +1 Of course! Serves me right for thinking through the problem too quickly! I'll remove it to avoid confusion. $\endgroup$ – user13888 Oct 20 '11 at 5:12
5
$\begingroup$

Your current attempt doesn't express $X-1$ as the sum of $B$ indicators. Instead, number the bad balls $1$ through $B$. Try $I_j = 1$ if bad ball $j$ is chosen before any of the good balls and $0$ otherwise. Then you have $X-1 = \sum_{j=1}^B I_j$. Now, can you finish off the problem by finding $E[I_j]$?

(Added, for completeness): We have $E[I_j] = \frac{1}{G+1}$, the probability that bad ball $j$ is chosen before any of the good balls. Thus $$E[X] = \frac{B}{G+1} + 1 = \frac{B + G + 1}{G+1} = \frac{N+1}{G+1}.$$

$\endgroup$
  • 1
    $\begingroup$ @caligirl11: No, $E(I_j)$ is the probability that bad ball $j$ is chosen before any of the good balls. This is not $B/N$. Instead, you have bad ball $j$ vs $G$ good balls; what's the probability that, out of those $G+1$ balls, the bad one is chosen first? $\endgroup$ – Mike Spivey Oct 20 '11 at 5:30
  • $\begingroup$ Ok thank you! I got it now E($I_j$)=1/(G+1). $\endgroup$ – caligirl11 Oct 20 '11 at 5:35
  • $\begingroup$ @caligirl11: Yep, nice job! $\endgroup$ – Mike Spivey Oct 20 '11 at 5:37
0
$\begingroup$

Since I was trying to solve this using summation techniques for curiosity, let me add my solution for documenting (even though it does not answer the question).

Let $P(n)$ be the probability that our first $n$ picks are bad candidates.

$$P(n) = {{(N-G)(N-G-1)(N-G-n+1)} \over {N(N-1)..(N-n+1)} }$$

We can re-arrange this equation in the following way.

$$P(n) = {{(N-G)(N-G-1)(N-G-n+1)(N-G-n)(N-G-n-1)..1(N-n)(N-n-1)..1} \over {N(N-1)..(N-n+1)(N-n)(N-n-1)..1}(N-G-n)(N-G-n-1)..1 }$$

$$P(n) = {{N-n \choose G} \over {N \choose G}}$$

TO calculate the expectation, let us define a function $F(n)$ which is the probability of failing $n-1$ times and succeeding $n^{th}$ time.

$$F(n) = P(n-1){G \over {N-n+1}}$$

$$E(x) = \sum_{i=1}^{N-G+1}iF(i)$$

Re-indexing this sum and applying the binomial identities leads to the result as expected.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.